Evaluasi Angkutan Lebaran 2008 dan Permasalahannya - Welly Pakan (Research and Development Agency of The Ministry of Transportation, 2009)
Idul Fitri day identic with return associated to this village and the increase of passenger transportation in the transportation of both land transportation, sea and air. Specifically for the calculation of the air passenger transportation is done starting at the H-7 until H+7, and with the know number of passengers who travel on the day of Idul Fitri in the country (domestic) have as many as 1,417,655 passengers, while the number of foreign passengers have as many as 288,960 passengers. On the day of Idul Fitri in 2008 the number of flights serving the airport In the country have as maw as 14 airports, while the number of flights serving the airport to have 4 overseas airports, namely Medan Polonia airport, Soekamo Hatta Airport Jakarta, Juanda Airport Surabaya and Ngurah Rai Denpasar.Many problems that occur during transportation of the Idul Fitri 2008 is the delay or delay the arrival and departure